DEVELOPMENT OF CRAFT EDUCATION IN KASHMIR VALLEY DURING THE RULE OF SULATAN ZAINUL AABIDEEN BUDSHAH - Reyaz Ahmad Bhat (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Abstract The paper explores the role of Sultan Zainul Aabideen in the development of craft education in the region of Kashmir. The study examines the Sultan's contribution towards preserving the traditional crafts of Kashmir and creating an environment that fostered innovation and creativity in the local craftsmen. The paper analyzes the initiatives taken by the Sultan to establish craft schools and workshops, provide training and support to craftsmen, and promote the products of the local artisans. The study also examines the impact of these efforts on the socioeconomic development of the region and the preservation of the cultural heritage of Kashmir. The findings of this research indicate that the Sultan's vision and commitment to craft education have played a crucial role in the development and promotion of traditional crafts in Kashmir, which has led to the growth of the local economy and the empowerment of the local artisans.